How to reduce turnover intention in team sports? Effect of organizational support on turnover intention of professional team sports athletes. Issue 2 (22nd February 2018) - Ströbel, Tim; Maier, Christopher; Woratschek, Herbert
Abstract : Purpose: Turnover of employees is a key challenge for companies. The same is true for sports clubs that must set appropriate incentives to decrease their athletes' turnover intention. As salary caps and team budgets restrict monetary incentives, the purpose of this paper is to investigate the effect of organizational support on turnover intention of professional team sports athletes. Design/methodology/approach: The paper applies a combined approach of qualitative and quantitative research and considers the specific requirements of European professional team sports. First, a qualitative study investigates organizational support in team sports and identifies relevant non-monetary incentives. Second, a quantitative study tests the effects of the identified organizational support incentives on turnover intention using a unique data set of professional team sports athletes. Third, a moderation analysis measures possible effects of age. Findings: Through the qualitative study, three relevant non-monetary incentives could be identified in the context of professional team sports: integration of family (IOF), second career support, and private problem support. The subsequent quantitative study of football, ice hockey and handball athletes assesses the effectiveness of the identified incentives. All three incentives negatively influence athletes' turnover intention, while IOF has a substantially stronger negative effect on turnover intention for younger athletes. Originality/value: The findings indicate the importance of organizational support to decrease athletes' turnover intention. Although money is relevant, sports clubs also need to address non-monetary incentives to decrease their athletes' turnover intention.